Pituitary gland volumes in patients with obsessive-compulsive disorder before and after cognitive-behavioral therapy - Atmaca, Murad; Yildirim, Hanefi; Yilmaz, Seda; Caglar, Neslihan; Baykara, Sema; Kekilli, Yasemin; Turkcapar, Hakan (Assoc Brasileira Psiquiatria, 2018)
Objective: The beneficial effects of psychopharmacological and cognitive behavioral therapy (CBT) on the brain are not well understood. In a previous study, we found smaller pituitary volumes in patients with obsessive-compulsive disorder (OCD). The purpose of this study was to examine the effect of CBT on pituitary gland volume. Methods: A total of 81 patients with various anxiety disorders and the same number of healthy controls underwent magnetic resonance imaging, and their pituitary gland volumes were compared at baseline. Pituitary gland volumes were also measured before and after CBT in the patient group. Results: OCD patients had smaller pituitary gland volumes at baseline than healthy controls (0.54 +/- 0.29 cm(3) for OCD patients vs. 0.82 +/- 0.30 cm(3) for healthy controls; p < 0.001). We found no significant changes in OCD patient pituitary gland volume after the 16-week treatment period, with mean pre- and post-treatment values of 0.54 +/- 0.29 cm(3) and 0.56 +/- 0.32 cm(3) , respectively (p > 0.05). Conclusion: Our results indicate an absence of post-CBT volumetric changes in the pituitary gland of OCD patients.
Keywords: Obsessive-compulsive disorder; cognitive behavioral therapy; pituitary gland; psychotherapy; neuroimaging